1973
DOI: 10.1210/jcem-37-5-826
|View full text |Cite
|
Sign up to set email alerts
|

STIMULATION OF INSULIN SECRETION BY GASTRIC INHIBITORY POLYPEPTIDE IN MAN.1

Abstract: The effect of very highly purified gastric inhibitory polypeptide (GIP) on insulin secretion in man was tested in normal volunteers. Administration of physiological doses of GIP together with glucose by IV infusion resulted in potentiation of the rise in IRI in the blood and improvement in glucose tolerance. It is concluded that GIP is a potent insulinotropic hormone and probably takes part in physiological potentiation of insulin secretion in response to hyperglycemia during absorption of nutrients from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
393
0
7

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 803 publications
(410 citation statements)
references
References 2 publications
4
393
0
7
Order By: Relevance
“…Thus GLP-1 resembles the biological action of gastric inhibitory polypeptide (GIP), also named glucose-dependent insulinotropic polypeptide, which as the best-established "incretin" candidate stimulates insulin release in a strictly glucose-dependent manner [14][15][16]. Compared with GIP in a similar experimental setting [11], GLP-1 reaches approximately 40% of the maximal insulin response caused by GIP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus GLP-1 resembles the biological action of gastric inhibitory polypeptide (GIP), also named glucose-dependent insulinotropic polypeptide, which as the best-established "incretin" candidate stimulates insulin release in a strictly glucose-dependent manner [14][15][16]. Compared with GIP in a similar experimental setting [11], GLP-1 reaches approximately 40% of the maximal insulin response caused by GIP.…”
Section: Discussionmentioning
confidence: 99%
“…The incretin function of GIP was first suggested by one study [19] and was confirmed in detailed clampstudies by another study [20]. Its function has been probed in immunoneutralization studies [21,22] and, more recently, in studies using a fragment, GIP 7-30amide, which turns out to be a GIP receptor antagonist [23], or antibodies to the GIP receptor [24].…”
Section: Glucose-dependent Insulinotropic Polypeptide (Gip)mentioning
confidence: 99%
“…Around 1973, the peptide gastric inhibitory polypeptide (GIP) had been shown to stimulate insulin secretion [10,11] and was henceforth called glucose-dependent insulinotropic polypeptide, thus preserving the acronym. It was also shown to be likely to function as an important incretin hormone in mimicry experiments [12], in which endogenous hormone concentrations are mimicked by infusion of exogenous hormone.…”
Section: Discovery Of Glucagon-like Peptide-1mentioning
confidence: 99%